Reasons as the Unity Among the Varieties of Goodness. (20th January 2015) - Rowland, Richard
Abstract: Our concepts of good simpliciter, good for, and good as a particular kind of thing must share some common element. I argue that all three types of goodness can be analysed in terms of the reasons that there are for a certain sets of agents to have pro‐attitudes. To this end I provide new and compelling accounts of good for and goodness of a kind in terms of reasons for pro‐attitudes that are more explanatorily illuminating than competing accounts and that evade the objections that undermine previous accounts of good for and goodness of a kind in terms of reasons.